The Semiotics of Textual Thresholds in the Poetic Space in Hisham Odeh’s Collection (Darj al-Atma) - A. Al-Rbeihat, Omar (Dirasat: Human and Social Sciences, 2024)
Objectives: The concern of this study is to analyze the textual thresholds in Hisham Awada’s "Darajul Atma" (The Stairs of Darkness) Diwan. It seeks to clarify their interaction with the theme of darkness and the poet’s loss of sight. It also aims at investigating the relationship between these thresholds and the textual span associated with the theme of darkness and the fuzziness of vision. Methods: The researchers employed a semiotic approach to analyze these textual thresholds by examining each threshold’s role in receiving poetic discourse and the poetic vision where the poet started his Diwan on one hand and represented them in the poetic text on the other. The study applied a descriptive analytical method to analyze these thresholds and the poetic texts. Results: The study reveals that there is a semiotic relationship between the textual thresholds as a semantic semiotic realization closely related to receiving the vision of darkness that the poet draws from in his collection. Additionally, the study indicates that there is a relationship between the significance of these thresholds, represented by the title "Darajul Atma" with the span of poetic text and its linguistic text. Conclusion: The study concluded that the theme of darkness and the poet’s loss of sight form a semiotic alignment with the textual thresholds and the poetic texts, where darkness, symbolized by the poet’s loss of sight, is associated with a range of psychological feelings and influences the poetic experience within this Diwan.